Quality Management of Islamic Educational Facilities Infrastructure: The Key to Improving The Quality of Learning - Latif, Abdul; Andriani, Novi; Kahfi, Sidik Al; Khumairah, Eka Silfia; Hakim, Arif Rahman; Latif, Muhammad Sabri (Yayasan Indonesia Emerging Literacy Education, 2025)
Islamic education has a strategic role in the development of national character, because it does not only emphasize cognitive aspects, but also instills spiritual, moral, and social values. In this context, Islamic educational units such as madrasahs and Islamic boarding schools require the support of quality facilities and infrastructure as a physical and instrumental foundation in supporting an effective and holistic learning process. This study aims to examine effective strategies for managing and improving the quality of facilities and infrastructure in Islamic educational units. to determine the effect of quality management of facilities and infrastructure on the quality of the learning process in Islamic educational units. This study uses a literature study method (library research) with documentation techniques and data analysis through reduction, presentation, and drawing conclusions from relevant sources. The results of the study indicate that quality management of facilities and infrastructure which includes planning, procurement, maintenance, supervision, and utilization of technology and cross-sector collaboration, has a significant effect on creating a conducive learning environment. Good facilities and infrastructure support increased motivation, welfare, and student achievement as well as the effectiveness of teacher teaching. Thus, quality management of educational facilities must be an integral part of the overall strategy for improving the quality of Islamic education, which balances academic goals and character building.